Body game - Mohamed Azanan, Muhammad Firdaus; Jumaat, Mohd Adam; Mazlan, Muhammad Alif Haikal; Mohd Ghazali, Siti Aswani; Zakaria, Abdul Rashid (Universiti Teknologi MARA, Kedah, 2018)
Teaching your kids about their body is very important. Activities that stimulate the senses help the brain to develop and function at its peak. Body games have influenced English, Science and mathematics learning for many years. Besides from motivating students to learn and improve their retention of the vocabulary taught, educational games also provide good ground to students to practice teamwork. Therefore, educational games should be widely used into the classroom and during the learning process, especially in Kindergarten as long as children love to play. The game that physically shown human body (children size). The players must label the part of the body. This game covers three subjects in 1 game, which are English, Mathematics and Science. Novelty and Uniqueness: